DATA AKUNTANSI DALAM MEMPREDIKSI KEBANGKRUTAN: PERSPEKTIF HISTORIS DAN KONTEMPORER - SALIS MUSTA ANI; AMELIA OKTRIVINA SIREGAR (Jurnal Bisnis dan Akuntansi, 2019)
This paper discusses the development of the use of accounting data in predicting corporate bankruptcy (financial distress) and the role of accounting data in predicting bankruptcy. Research completion will be divided into several developments, covering the 1930s until the 2000s.